Characterization of an underwater channel for quantum communications in the Ottawa River - Hufnagel, Felix; Sit, Alicia; Grenapin, Florence; Bouchard, Frederic; Heshami, Khabat; England, Duncan; Zhang, Yingwen; Sussman, Benjamin J.; Boyd, Robert W.; Leuchs, Gerd; Karimi, Ebrahim (Optics Express, 2019)
We examine the propagation of optical beams possessing different polarization states and spatial modes through the Ottawa River in Canada. A Shack-Hartmann wavefront sensor is used to record the distorted beam’s wavefront. The turbulence in the underwater channel is analysed, and associated Zernike coefficients are obtained in real-time. Finally, we explore the feasibility of transmitting polarization states as well as spatial modes through the underwater channel for applications in quantum cryptography.
CRIS-Team Scopus Importer:2023-04-20